2021
DOI: 10.1177/10781552211027945
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine induced Steven–Johnson syndrome: A rare case report

Abstract: Introduction Steven–Johnson syndrome (SJS) is a serious mucocutaneous reaction, characterized by fever, influenza-like symptoms and followed by dermatological manifestations. Capecitabine is an oral fluoropyrimidine carbamate analogue of 5-Fluorouracil (5-FU). It is widely accepted for many malignancies because of its better safety profile and tolerability. Hand-foot syndrome is the common dermatological toxicity associated with Capecitabine and SJS is the rarest manifestation. Case presentation: We report a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The current series included 16 patients who underwent radiochemothreapy, i.e., concurrent radiation and cytotoxic chemotherapy. Nevertheless, there are quite a few reports of EM or EM‐like rash induced by cytotoxic chemotherapeutic drugs 14–16 . In these cases of EM/SJS/TEN that arose during cytotoxic chemotherapy, the patient had previously undergone RT before rash onset, raising some doubt that the rash was elicited truly by RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current series included 16 patients who underwent radiochemothreapy, i.e., concurrent radiation and cytotoxic chemotherapy. Nevertheless, there are quite a few reports of EM or EM‐like rash induced by cytotoxic chemotherapeutic drugs 14–16 . In these cases of EM/SJS/TEN that arose during cytotoxic chemotherapy, the patient had previously undergone RT before rash onset, raising some doubt that the rash was elicited truly by RT.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are quite a few reports of EM or EM-like rash induced by cytotoxic chemotherapeutic drugs. [14][15][16] In these cases of EM/SJS/TEN that arose during cytotoxic chemotherapy, the patient had previously undergone RT before rash onset, raising some doubt that the rash was elicited truly by RT. Moreover, in the current series, rash did not relapse in all cases who experienced additional chemotherapy cycles.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] General SJS/TEN can be relieved after treatment with glucocorticoids and immunoglobulin, but it will be life-threatening when the disease is serious or not timely diagnosed and treated. Kavya Karthikeyan et al [ 39 ] reported a serious case of SJS. A 70-year-old male patient was diagnosed with adenocarcinoma of the pancreas, stage 4 and started on chemotherapy with Capecitabine.…”
Section: Discussionmentioning
confidence: 99%